Detention by the Commanding Officer (ANKUM) in the Investigation of Military Offences: Problematizing Authority Through a Due Process of Law Analysis - Situmorang, Irvan Saputra; Istiqomah, Milda (International Journal of Business, Law, and Education, 2026)
This article examines the authority of the Commanding Officer with disciplinary power (Atasan yang Berhak Menghukum or ANKUM) to order detention during the investigation of military offences in Indonesia and evaluates its compatibility with the principle of due process of law. The problem is fundamentally structural: although Law No. 31 of 1997 recognizes ANKUM, Military Police, and Oditurs as investigators, the law simultaneously places decisive detention authority in the hands of ANKUM, while Military Police or Oditurs often perform the actual investigative work. This design creates a normative overlap between command authority and criminal process, thereby generating risks of conflict of interest, impaired investigative independence, and procedural unfairness. Using a normative juridical method based on statutory, comparative, and conceptual approaches, this article argues that detention by ANKUM is difficult to reconcile with due process requirements of impartiality, objectivity, and institutional independence. A comparison with the United States military justice system shows a different model: pretrial confinement is constrained by probable cause, neutral review, and anti-command-influence safeguards. The article therefore proposes a reconstruction of Indonesian military procedural law by transferring detention authority to Military Police or Oditurs, limiting ANKUM to administrative notification and disciplinary supervision, and introducing an explicit prohibition on command interference in criminal investigations.